URGENSI PENGATURAN DO NOT RESUSCITATE (DNR) DALAM SISTEM HUKUM KESEHATAN DI INDONESIA - Rizka Rizka; Friska Azharun Tyas Ardellia; Yusril Aulia Patra (JOURNAL IURIS SCIENTIA, 2026)
This study examines the Do Not Resuscitate (DNR) regulation in global health law and the urgency of its establishment in Indonesia. This study uses a normative approach with descriptive-analytical specifications through both statutory and conceptual approaches. The data sources used include primary legal materials, namely the 2023 Health Law, Minister of Health Regulation Number 37 of 2014, and the Indonesian Code of Medical Ethics (KODEKI), as well as secondary legal materials in the form of books, journals, and previous research. The results of the study indicate that: (1) DNR regulation at the global level has developed steadily, including through international instruments such as the Universal Declaration of Human Rights (1948) and the International Conference on Medical Ethics (2024), as well as regulations in various developed countries, such as the Uniform Health-Care Decisions Act in the United States (through the POLST scheme), the Mental Capability Act in the United Kingdom (through DNACPR), and Advance Care Planning in Japan; (2) In Indonesia, DNR regulations are still implicit, reflected in the Health Law (Articles 276 and 293) and the Minister of Health Regulation (Article 14), thus giving rise to legal, potential criminal risks under the Criminal Code (Articles 458 and 474), and ethical conflicts in medical practice. The urgency of establishing DNR regulations in Indonesia is based on a human rights perspective, the Beauchamp-Childress bioethics principle, and the theory of legal positivism.